1997
DOI: 10.1021/ja962499w
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Oxidation State and Coordination Geometry of Metal Ions in Azurin

Abstract: The small electron transporting copper protein, azurin, has been studied in order to investigate the interplay between the oxidation states of the metal and its coordination geometry. The results show that the metal coordination geometry for Ag(I) in Ag(I) substituted wild type azurin is only slightly different from the geometry for Cd(II) in cadmium substituted azurin both being similar to the geometry for copper in native azurin. Furthermore, the coordination geometry for Ag(I) in the Met121 to Leu substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 21 publications
0
58
0
Order By: Relevance
“…Thus, one function of the methionine might be to prevent a water molecule from entering the metal ion binding site. 27,33 methionine does not take part in bonding to the metal but appears to stabilize the metal geometry was also supported by 199m Hg studies of azurin. 45,46 For references to studies of other mutants of azurin, please refer to Table 3.…”
Section: Comparison Of Model Calculations and Experimentsmentioning
confidence: 77%
See 1 more Smart Citation
“…Thus, one function of the methionine might be to prevent a water molecule from entering the metal ion binding site. 27,33 methionine does not take part in bonding to the metal but appears to stabilize the metal geometry was also supported by 199m Hg studies of azurin. 45,46 For references to studies of other mutants of azurin, please refer to Table 3.…”
Section: Comparison Of Model Calculations and Experimentsmentioning
confidence: 77%
“…This was later expanded by a PAC study using 111 Ag on wild-type azurin as well as Met121Leu-azurin of P. aeruginosa. 33 In Figure 8, the Fouriertransformed PAC spectra of Ag-azurin, Cd-azurin, Ag-Met121Leu-azurin, and Cd-Met121Leu-azurin are compared. A comparison clearly shows that for wildtype azurin metal substitution with Ag or Cd results in almost the same structure.…”
Section: Structure Of Metal Ion Binding Site In Blue Coppermentioning
confidence: 99%
“…A relaxation of a Ag͑I͒ geometry in to a Cd͑II͒ geometry has also been observed in the copper protein, azurin, within a time scale of about 100 ns. 1 The present study is the first time that the full NQI tensor has been determined for a Cd͑II͒ complex experimentally as well as by ab initio calculations. Perspectives includes PAC experiments on single crystals of metal containing proteins, providing the full NQI tensor, thereby increasing the information content.…”
Section: Discussionmentioning
confidence: 87%
“…Similar investigation performed on the copper protein azurin showed that the coordination geometry for Ag͑I͒ relaxes to the geometry of Cd͑II͒ on a time scale of about 100 ns at 25°C. 1 Applying perturbed angular correlation of ␥-ray ͑PAC͒ spectroscopy to a single crystal allows for the determination of the full nuclear quadrupole interaction ͑NQI͒ tensor in contrast to experiments on randomly oriented molecules, where only the eigenvalues of the tensor are obtained. Previous work on the determination of the NQI tensor has been performed with various experimental techniques including PAC, NMR, and electron-nuclear double resonance ͑EN-DOR͒ spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation